(untitled) (Journal of the College of Basic Education, 2026)
Individual personal skills are among the vital and important matters that have positive effects on individuals, especially on women in particular, as women’s acquisition of some skills, especially in societies that are built on the basis of gender roles, or patriarchal authority, helps enhance their personal empowerment, which subsequently leads them to achieving their economic independence and even strengthening their social position. In her novel Jane Eyre (1847), Charlotte Brontë (1816 – 1855), the English novelist and poet, promotes amongst her other themes, the theme of individual skills as a means of economic solidness through an exploration of the life journey of an orphan girl, Jane, whose individual skills have helped her to overcome life’s difficulties, withstand the hardships, and eventually bring her somewhat to safety. Ultimately, the novelist aims to show how the issue of an individual’s possession of skills is related to success in life, especially for women.